PENGARUH PENDIDIKAN KEWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN EKSPEKTASI PENDAPATAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA (STUDI PADA MAHASISWA AKUNTANSI UNIVERSITAS PATTIMURA AMBON) - Siompo, Fitriyani; Sososutiksno, Christina; Laitupa, Muhammad Fadillah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
Through entrepreneurship, one can provide jobs for the community. Currently, with formal education about entrepreneurship, it is expected that students will have an interest in entrepreneurship. Therefore, by having students' interest in entrepreneurship, it encourages the creation of new jobs which ultimately create prosperity. This study aims to determine the effect of Entrepreneurship Education, Family Environment and Income Expectations on Students' Interest in Entrepreneurship. Studies on Accounting Students at Pattimura University, Ambon. The number of respondents used in this study was 87 students of the Department of Accounting, Faculty of Economics and Business, Pattimura University, Ambon, class of 2020 who had passed the entrepreneurship course. In this study using descriptive statistical tests, classical assumption tests and hypothesis testing using the regression model, namely multiple linear regression. This study states that Entrepreneurship Education and Income Expectations have no significant effect on Student Entrepreneurial Interests. Meanwhile, the Family Environment has a significant influence on Student Entrepreneurial Interests